The effect of terahertz electromagnetic radiation on cardiovascular system and orbital vessels in age-related macular degeneration - K. U. Eremenko; V. F. KirichukІ; L. E. Fedorischeva (Oftalʹmologiâ, 2014)
Aim.To study the effect of terahertz (THz) radiation at atmospheric oxygen frequency (129 GHz) on cardiovascular and hemodynamic parameters of orbital arteries following the irradiation of bioactive points in healthy volunteers and age-related macular degeneration (AMD) patients.Materials and methods. 18 healthy volunteers (36 eyes) and 20 AMD patients (34 eyes) were examined. Blood pressure (BP), heart rate (HR), systolic and diastolic blood flow velocities, resistance index (RI) in orbital arteries before and following THz radiation of two bioactive points VB1 and TR23 at atmospheric oxygen frequency 129 GHz in continuouswave generation mode were measured.Results. First data on the effect of THz waves at atmospheric oxygen irradiation and absorption molecular spectrum frequency (129 GHz) in continuous wave generation mode on ocular hemodynamics in healthy persons and AMD patients are presented. Following THz irradiation at atmospheric oxygen frequency (129 GHz), common hemodynamicparameters (BP, HR) decreased. In healthy volunteers, systolic and diastolic BP reduced by 22.83±4.09 and 8.82±0.98 mm Hg, respectively (р<0.05), HR reduced by 6.11±0.15 bpm (р<0.05). In AMD patients, systolic and diastolic BP significantly decreased by 45.55±0.43 and 9.56±1.42 mm Hg, respectively (р<0.05), HR decreased by 6.15±1.1 bpm (р<0.05). In AMD patients, systolic blood flow velocity significantly reduced by 2.89±0.1 cm / sec in central retinal artery and increased by0.9‑5.97 cm / sec in short posterior ciliary arteries and ophthalmic artery. RI in these vessels decreased by 0.13, 0.11, 0.13 and 0.12, respectively.Conclusion. THz waves at atmospheric oxygen irradiation and absorption molecular spectrum frequency (129 GHz) are safe and cause no side effects on general health of healthy volunteers and AMD patients. Besides, this method improves ocular hemodynamics.